Engagement in a pilot produce prescription program in rural and urban counties in the Southeast United States - Owens, Caroline E.; Cook, Miranda; Reasoner, Tammy; McLean, Aleta; Webb Girard, Amy (Frontiers in Public Health, 2024)
Introduction In the United States, over one in every ten households experiences food insecurity. Food insecurity is associated with often co-occurring adverse health consequences, including risk for obesity, type 2 diabetes, and hypertension. Within the “Food is Medicine” intervention space, Produce Prescription Programs (PRx) seek to alleviate food insecurity and improve diet and health outcomes by leveraging access to produce through healthcare organizations. Though these programs are burgeoning across the United States, research surrounding their implementation and outreach is limited. Methods This study evaluates the implementation, reach, engagement, and retention of a PRx program piloted in two regions of Georgia (US) from 2020 to 2022. The study included 170 people living with one or more cardiometabolic conditions recruited from clinical sites in metropolitan and rural areas. The program provided pre-packaged produce boxes and nutrition education over six months. We examine participants’ baseline demographics, food security status, dietary patterns, and loss to follow-up across contexts (metropolitan and rural). We employ regression analyses and model comparison approaches to identify the strongest predictors of loss to follow-up during the pilot period. Results In the pilot period of this program, 170 participants enrolled across rural and metropolitan sites. Of these, 100 individuals (59%) remained engaged for the six-month program. While many individuals met the target criteria of living with or at-risk of food insecurity, not all lived with low or very low food security. Metropolitan participants, males, and those with children in the household had significantly higher odds of loss to follow-up compared to rural participants, females, and those without children in the household. No other significant demographic or household differences were observed. Discussion This study demonstrates the potential of PRx programs to enhance food and nutrition security and cardiometabolic health in metropolitan and rural clinical settings. Future research should focus on addressing barriers to engagement and expanding the reach, impact, and sustainability of PRx programs across diverse contexts.